STUDY OF AN ADD-DROP FILTER USING A SINGLE BRAGG COUPLER - Rustam E. Siregar -; Ayi Bahtiar -; A. Abrar - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2007)
An add-drop filter that consists of a planar directional coupler with a single Bragg grating in one of its arms was studied. The calculation was based on coupled-mode equations in the form of a matrix equation by considering the studied structure. From the matrix equation, the propagation factors as eigenvalues of the eigenmodes was obtained, while the spatial structures of the eigenmodes are determined by the eigenvectors of the coupling matrix. By use of boundary conditions in individual waveguides, the drop output, return loss and total transmission, respectively, was calculated at the Bragg wavelength of 1550 nm. The results satisfy the requirements for Wavelength Division Multiplexing (WDM) applications.Keywords : Bragg grating, add-drop filter, coupled mode equation, matrix equation